Biomimetic Interfaces Reveal Activation Dynamics of C‐Reactive Protein in Local Microenvironments. Issue 11 (4th April 2014) - Goda, Tatsuro; Kjall, Peter; Ishihara, Kazuhiko; Richter‐Dahlfors, Agneta; Miyahara, Yuji
<x xml:space="preserve">Abstract</x> A cell‐membrane‐mimetic surface with an organic bioelectronic ion pump system creates an in vitro situation that replicates the pathogenic progression on a sensing platform to investigate the molecular dynamics of C‐reactive protein (CRP) to its receptor on cell membrane changes by local microenvironments in acute phase of inflammation and infection. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>